Sistem Pendukung Keputusan Pemilihan Apartemen Terbaik Menerapkan Metode TOPSIS dan Pembobotan ROC - Firdo Andri Saputra; Agus Iskandar (Journal of Information System Research (JOSH), 2023)
An apartment is a residential unit or place to live in a high-rise building, usually consisting of several floors or levels. Choosing an apartment is very difficult because there are many factors that must be considered in choosing the apartment. In Jakarta Selatan City, there are many apartments, because each apartment has its own conditions and charm. There are problems with apartment buyers because of the variety of facilities available, so buyers are confused about choosing which apartment is most suitable for them. So by implementing a system that can help decisions and provide recommendations for apartments that are suitable for customers. This research has 5 criteria, namely: Price, Size, Cost, Facilities and Location. Therefore, by implementing a Decision Support System using the TOPSIS method and ROC weighting which can produce weight values and produce ranking values which can help in solving the problems in this research. So the one chosen in the selection of the best alternative apartment A5 was the Denpasar Residence with a value of 0.8396